Pengaruh Sumber Karbon Terhadap Daya Antagonistik Bakteri Pseudomonas Pendar Fluor Terhadap Erwinia Carotovora - Hardian Susilo ADDY (Fakultas Pertanian Universitas Jember, 2008)
This research was conducted to study antimicrobial stimulation of fluorescentpseudomonad to inhibit Erwinia carotovora. We used several carbon sources to stimulateantimicrobial substances from fluorescent pseudomonad that available to inhibit E.carotovora in vitro.The results shown that mannitol 10% was the best stimulant agent to increase antagonistics offluorescent psudomonad againts E. carotovora. Also, mannitol increased antimicrobial substancestwohold compared with control without stimulant agent. Detection of antimicrobial substance usingTLC showed that only one antimicrobial was detected with retention factor (Rf) of 0,68. However,identtification and characterisation of that substance is needed.